Faktor-Faktor Keterlambatan Penderita Kanker Payudara dalam Melakukan Deteksi Dini di RSUD Sanjiwani Gianyar Bali - Made Adwitya Krisna Kinasih; Sang Nyoman Suriana; Dewa Ayu Agung Alit Suka Astini (Aesculapius Medical Journal, 2023)
Breast cancer is the number one cancer mortality factor for women worldwide. Until now, it is not known with certainty what factors trigger the occurrence of breast cancer and there is no specific treatment that can be carried out in the context of preventing breast cancer. Generally, breast cancer patients go to the doctor when the condition is too late and the prognosis is poor. Early detection is the only action to feel the emergence of this disease as soon as possible. The purpose of this research is to identify the description of the factors of delay in early detection of breast cancer including age, education, occupation, socioeconomic, and level of knowledge. This study includes a descriptive, cross-sectional design conducted at the Sanjiwani Hospital, Gianyar Regency, Bali from June-July 2021. The research variables are age, education, occupation, socioeconomic, and level of knowledge. The number of respondents is 49 people. Data collection applied purposive sampling method from patients who came to the Surgical Polyclinic of RSUD Sanjiwani. Data was collected by filling out questionnaires and analyzed using descriptive analysis. The results show that the majority of respondents are 40-49 years old (40.8%), have high school education (40.8%), do not work (55%), have a low socioeconomic level (89.8%), and have less knowledge (44. 9%) regarding breast cancer. The conclusion of this study is a large number of breast cancer sufferers who are late for early detection at the Sanjiwani Hospital aged 40-49 years, have high school education, do not work, have low socioeconomic levels, and have less knowledge about breast cancer.